2020
DOI: 10.1116/1.5135504
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive artifacts revealed from magnetometry measurements of rare earth-transition metal thin films

Abstract: Note: This paper is part of the Special Topic Collection on 30 years of the Nellie Yeoh Whetten Award -Celebrating the Women of the AVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Together, these results provide important insights into the proximity of T A C and T M for alloy design. On account of the calculated values of ∆S mag for the current study, we observed similar values for CCIF-FH and MRIT as in line with other studies [11,14,20,[23][24][25][26], however, there exists a discrepancy between the calculated values of ∆S mag for and CCIF-FC and MRIT. This is mainly because a smaller amount of the sample is allowed to convert to martensite at 5 T during the FH process with respect to FC process which is shown in figure 3(b).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Together, these results provide important insights into the proximity of T A C and T M for alloy design. On account of the calculated values of ∆S mag for the current study, we observed similar values for CCIF-FH and MRIT as in line with other studies [11,14,20,[23][24][25][26], however, there exists a discrepancy between the calculated values of ∆S mag for and CCIF-FC and MRIT. This is mainly because a smaller amount of the sample is allowed to convert to martensite at 5 T during the FH process with respect to FC process which is shown in figure 3(b).…”
Section: Resultssupporting
confidence: 89%
“…Sample mass was determined with 0.01 mg accuracy before the magnetic measurements and placed into plastic capsules and measured with a contamination-free half-cylinder brass sample holder. Contamination and the reproducibility of the measurements were regularly controlled as described in [20].…”
Section: Methodsmentioning
confidence: 99%
“…Magnetometry measurements. The bulk magnetic properties of the samples were determined 38 by vibrating sample magnetometry (VSM) using a 7 T Quantum Design system. The measurements were performed at 300 K for both in-plane and out-of-plane geometries and in fields of up to 4 T. All samples were measured using the same VSM holder and each measurement was repeated several times.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements were performed at 300 K for in-plane (IP) and out-of-plane (OOP) sample geometries and in fields of up to 2 T. All samples were measured by using the same VSM holders (i.e., one dedicated for IP and another one for OOP measurements). In addition, the background signal coming from the VSM holder and bare Si substrates was periodically checked to ensure a clean magnetic signal coming from only the trilayers or from the individual FM and FI layers.…”
Section: Methodsmentioning
confidence: 99%